2009
DOI: 10.1002/med.20158
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal chemistry and therapeutic potential of muscarinic M3 antagonists

Abstract: Muscarinic acetylcholine receptors belong to the G-protein-coupled receptors family. Currently five different receptor subtypes have been identified and cloned. M3 receptor subtypes are coupled to G(q) family proteins and increase phosphatidyl inositol hydrolysis and calcium release from internal stores. They are widely distributed both in the central nervous system and in the periphery. At the central level, M3 receptor subtypes are involved in modulation of neurotransmitter release, temperature homeostasis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 108 publications
1
19
1
2
Order By: Relevance
“…Our results have shown that M3 subtype, but not other muscarinic receptors, mediated the cell proliferation stimulated by exogenous or endogenous ACh. The M3 receptor, which selectively conjugate to the G proteins of the Gq family, could transactivate several second messengers and modulate numerous fundamental functions in central and peripheral nervous system3031. Recent years, increasing evidences demonstrated that M3R may play a vital role in the carcinogenesis of many types of cancer, including colon cancer, lung cancer, and cholangiocarcinoma323334.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have shown that M3 subtype, but not other muscarinic receptors, mediated the cell proliferation stimulated by exogenous or endogenous ACh. The M3 receptor, which selectively conjugate to the G proteins of the Gq family, could transactivate several second messengers and modulate numerous fundamental functions in central and peripheral nervous system3031. Recent years, increasing evidences demonstrated that M3R may play a vital role in the carcinogenesis of many types of cancer, including colon cancer, lung cancer, and cholangiocarcinoma323334.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins play a pivotal role in the regulation of many physiological functions both in the central and in the peripheral nervous systems [1]. Like other GPCRs, these proteins exhibit a basal activity that is increased by the action of its natural agonist acetylcholine.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we focus on the human M3 muscarinic acetylcholine receptor (M3R), which is involved in modulation of neurotransmitter release, temperature homeostasis, and food intake in the central nervous system, as well as in the induction of smooth muscle contraction, gland secretion, indirect relaxation of vascular smooth muscle in the peripheral nervous system [1]. M3R is arranged in the distinctive seven-transmembrane (TM) helix bundle architecture like all GPCRs, with its N-terminus located on the extracellular side of the plasma membrane and the C-terminal tail in the cytoplasmic side.…”
Section: Introductionmentioning
confidence: 99%
“…There is still a need for safer M3 antagonists for the treatment of OAB. New selective M3R antagonists currently in early discovery and under development have been designed to address these issues [21]. …”
Section: Muscarinic Receptorsmentioning
confidence: 99%